Dirichlet Problem for the Stokes Flow Function in a Simply-Connected Domain of the Meridian Plane - Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We develop a method for the reduction of the Dirichlet problem for the Stokes flow function in a simply-connected domain of the meridian plane to the Cauchy singular integral equation. For the case where the boundary of the domain is smooth and satisfies certain additional conditions, the regularization of the indicated singular integral equation is carried out.